Perbandingan osteoporosis berdasarkan radiomorfometri panoramik antara mandibular cortical index dengan panoramic mandibular index pada pasien di Rumah Sakit Gigi Mulut Universitas Hang Tuah - Sarianoferni .; Endah Wahjuningsih (Makassar Dental Journal PDGI Makassar, 2018)
Dentists have an important role in detecting osteoporosis that can be found incidentally on radiographic panoramic examination. Radiomorfometri mandible on panoramic radiography is a simple technique for screening osteoporosis and provides additional benefits for patients with radiographic examination for oral care. This study used a sample aged 35 years and over because the theory is based on the influence of estrogen hormone responsible for the regulation of calcium levels in the blood which begin to decline levels in the body since the age of 35 years. Radiomorfometri used were mandibular cortical index (MCI) and panoramic mandibular index (PMI). Each of these has a different way of identifying osteoporosis by panoramic. The sample of this cross-sectional study, with analytic observational study design is the total sampling, ie all data panoramic radiographs of patients over the age of 35 years and over who come to the Hang Tuah University Hospital Surabaya and required panoramic radiographs for dental and oral care needs, and in accordance with the criteria. The results of the Mann Whitney test showed no significant difference with p = 0.624 (p> 0.05), which means that there is no significant difference between the results of os teoporosis based on MCI and PMI. It is concluded that there was no significant difference between the results of osteoporosis based on radiomorfometri MCI and PMI on Hang Tuah University Hospital patients.